STRATEGI PENGEMBANGAN PRODUK DAN PERHITUNGAN HARGA POKOK PRODUKSI PADA USAHA HOME INDUSTRY KERIPIK PISANG SALAI IBU HERYATI - Hesti Akmariani, Hesti Akmariani; Mubarak2, Husni Mubarak (Politeknik Negeri Jakarta, 2024)
This research aims to understand how the quality of the Smoked Banana Chips product from Keripik Pisang Salai Ibu Heryati Business can improve and determine the calculation of the production cost of the business. This study is descriptive research using a qualitative descriptive approach. The research data were obtained from the owner of Keripik Pisang Salai Ibu Heryati Business. Data collection techniques included interviews and document studies. The research results indicate that in product development strategy, the strategies implemented by Keripik Pisang Salai Ibu Heryati include improving existing products, adding new products, and imitating competitor strategies. There are eight systematic stages in the process of developing a new product carried out by this business, namely idea collection, screening, concept development and testing, marketing strategy development, business analysis, product development, market testing, and commercialization stages. However, the market testing and commercialization stages have not been implemented. The calculation of the production cost of Keripik Pisang Salai is done using the process costing method with a variable costing approach. The purpose is to provide an accurate comparison in determining effective production decisions in a relatively short time. The determination of the selling price charged to consumers is based on the expected profit estimate of Ibu Heryati Business to meet operational needs and achieve more adequate profits. Keywords: Product Development; Product Cost Calculation; Kripik Pisang; Bengkalis